The social dynamics of family violence - Hattery, Angela (Westview Press, 2017)
"This compelling text explores family violence throughout the life course, from child abuse and neglect to intimate partner violence and elder abuse. Paying special attention to the social character and institutional causes of family violence, Hattery and Smith ask students to consider how social inequality, especially gender inequality, contributes to tensions and explosive tendencies in family settings. Students learn about individual preventative measures and are also invited to question the justice of our current social structure, with implications for social policy and reorganization. The second edition features a new chapter focusing on institutionalized violence affecting families of the military and police, as well as a discussion on sports and sexual abuse cases occurring on college campuses. Hattery and Smith also examine violence against women globally and relate this to violence in the United States. Unique coverage of same-sex and multicultural couples, as well as of theory and methods, make this text an essential element of any course considering the sociology of family violence"--